Aerospace series. Bearing, spherical plain, in corrosion resisting steel with self-lubricating liner, low starting torque and low friction coefficient, elevated duty cycles under low oscillations at different operating conditions, wide series. Dimensions and loads Part 2, (31st October 2019) - British Standards Institution,
No abstract available